Analisis Kebijakan Manajemen PjBL Jurnal Pagi untuk Mengoptimalkan Kemandirian Anak Usia Dini TK Ar Rahman Jombang - Katon Aisyiah; Muhamad Sholeh; Mufarrihul Hazin; Budi Purwoko; Amrozi Khamidi (JCE (Journal of Childhood Education), 2026)
This study aims to analyze the Project Based Learning (PjBL)-based learning management policy through the Morning Journal Program in optimizing the independent character of early childhood at Ar Rahman Kindergarten, Jombang. This study departs from the need for innovative, structured, and responsive learning policies to foster independence and literacy from an early age. The study uses a descriptive qualitative approach with a policy analysis method, referring to the William Dunn (2003) model which includes six dimensions: policy content, agenda setting, formulation, actors, implementation, and evaluation. Data were collected through observations, interviews, and program document reviews, then analyzed thematically according to the policy dimensions. The results show that the integration of PjBL through the Morning Journal Program effectively encourages children's independence through activities that require responsibility, initiative, simple decision-making, and independent task completion. The success of the program is influenced by the commitment of teachers in planning and mentoring, parental involvement in strengthening habits at home, and support for a conducive learning environment. These findings confirm that the PjBL-based Morning Journal Program has the potential to be an applicable strategy for PAUD institutions to shape children's independent character sustainably.